Time-reversed measurement of the 18Ne(α,p)21Na cross-section for Type I X-ray bursts - Salter, Philip James Charles (The University of Edinburgh, 2012)
Type I X-ray bursts (XRB) are highly energetic and explosive astrophysical events, observed as very sudden and intense emissions of X-rays. X-ray bursts are believed to be powered by a thermonuclear runaway on the surface of a neutron star in a binary system. XRB models are dependent on the accurate information of the nuclear reactions involved. The 18Ne(α,p)21Na reaction is considered to be of great importance as a possible breakout route from the Hot-CNO cycle preceding the thermonuclear runaway. In this thesis work, the 18Ne(α,p)21Na reaction cross-section was indirectly measured at Ecm(α,p) = 2568, 1970, 1758, 1683, 1379 and 1194 keV, using the time-reverse 21Na(p,α)18Ne reaction. Since the time-reverse approach only connects the ground states of 21Na and 18Ne, the cross sections measured here represent lower limits of the 18Ne(α,p)21Na cross-section. An experiment was performed using the the ISAC-II facility at TRIUMF, Vancouver, Canada. A beam of 21Na ions was delivered to a polyethylene (CH2)n target placed within the TUDA scattering chamber. The reaction 18Ne and 4He ions were detected using silicon strip detectors, with time-of-flight and ΔE/E particle identification techniques used to distinguish the ions from background. The measurement at Ecm = 1194 keV is the lowest energy measurement to date of the 18Ne(α,p)21Na cross section. The measured cross sections presented in this thesis were compared to the NON-SMOKER Hauser-Feshbach statistical calculations of the cross section and to the unpublished results of another time-reverse investigation performed by a collaboration at the Argonne National Laboratory. A 18Ne(α,p)21Na reaction rate calculation based on the measured cross sections was performed. In comparison with previous reaction rate estimates, our results indicate a rate that is about a factor 2-3 lower than Hauser-Feshbach calculations, suggesting that a statistical approach may not be appropriate for cross section calculations for nuclei in this mass region. The astrophysical consequences of our new results appear to remain nevertheless negligible. These are also presented in this thesis.
Keywords: x-ray burst; nuclear reaction; cross section